2010
DOI: 10.1111/j.1471-0528.2009.02475.x
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes mellitus screening and diagnosis: a prospective randomised controlled trial comparing costs of one‐step and two‐step methods

Abstract: Objective To conduct a cost minimisation analysis of three methods of gestational diabetes mellitus (GDM) screening and diagnosis.Design Prospective randomised controlled trial.Setting University teaching hospital.Population Pregnant women (n = 1594) presenting for GDM screening.Methods Women presenting for GDM screening, who consented to participate, were randomised to GR1 [1-hour, 50-g glucose screen (GS) ± 3-hour, 100-g oral glucose tolerance test (OGTT)], GR2 (50-g GS ± 2-hour, 75-g OGTT) or GR3 (2-hour, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
1
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(63 citation statements)
references
References 27 publications
2
54
1
5
Order By: Relevance
“…Regarding the cost-effectiveness of various procedures, a randomised cost-minimisation analysis found that one-step screening (2 h OGTT, Canadian Diabetes Association criteria) was more expensive than two-step approaches including a glucose challenge test based on time expenditure and analyses of multiple blood samples [36]. Another very recent decision analysis suggested that the IADPSG criteria are cost-effective, if post-delivery care is accomplished aiming to reduce diabetes incidence at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the cost-effectiveness of various procedures, a randomised cost-minimisation analysis found that one-step screening (2 h OGTT, Canadian Diabetes Association criteria) was more expensive than two-step approaches including a glucose challenge test based on time expenditure and analyses of multiple blood samples [36]. Another very recent decision analysis suggested that the IADPSG criteria are cost-effective, if post-delivery care is accomplished aiming to reduce diabetes incidence at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 50% of women with GDM will become will become overt diabetes (Type-2) over a period of 5 -20 years [3]. Depending on geographical location and diagnostic methods used, the prevalence of GDM varied from 3.8% -21% in different parts of the India [4]. As Asian ethnic background has been identified as a risk factor, and hence, screening should be offered to all pregnant women for GDM [5].…”
Section: Introductionmentioning
confidence: 99%
“…Approximate costs are $6-$8 for A1C, 38 $6-$10 for a fasting blood glucose test 39 and $30 for an oral glucose tolerance test. 40 …”
Section: Screening Test In Practicementioning
confidence: 99%